Promoting good health research practice in low- and middle-income countries. Issue 1 (1st December 2016) - Mahendradhata, Yodi; Nabieva, Jamila; Ahmad, Riris Andono; Henley, Patricia; Launois, Pascal; Merle, Corinne; Maure, Christine; Horstick, Olaf; Elango, Varalakshmi
Abstract : Background: Good clinical practice (GCP) guidelines have been the source of improvement in the quality of clinical trials; however, there are limitations to the application of GCP in the conduct of health research beyond industry-sponsored clinical trials. The UNICEF/UNDP/World Bank/WHO Special Program for Research and Training in Tropical Disease is promoting good practice in all health research involving human through the Good Health Research Practice (GHRP) training program initiative. Objective: To report the results of piloting the GHRP training program and formulate further steps to harness GHRP for promoting good practices in all health research involving human, particularly in low- and middle-income countries (LMICs). Design: The objective of this training is to impart knowledge and skills for the application of ethical and quality principles to the design, conduct, recording, and reporting of health research involving human participants based on the level of risk, to ensure a fit-for-purpose quality system. This has been formulated into five sequential modules to be delivered in a 4-day course. Four courses have been organized in the pilot phase (2014–2015). The courses have been evaluated and assessed based on course feedback (quantitative and qualitative data) collected during course implementation and qualitative email-based pre- and post-course evaluation. Results: Participants were highly satisfied with the course content and its organization. The relevance and applicability of the course content resulted in positive feedback and an articulated willingness to adapt and disseminate the course. Action points to strengthen the training program have been identified, and showed the imminent need to develop a consensus with a broader range of key stakeholders on the final set of GHRP standards and means for implementation. Conclusions: There is an urgent need to harness the momentum to promote high-quality and ethical health research in LMICs through scaling up GHRP training and further development of GHRP principles into international standards.